2021
DOI: 10.1177/2333721421993754
|View full text |Cite
|
Sign up to set email alerts
|

Using Everyday Technology Independently When Living with Forgetfulness: Experiences of Older Adults in Barcelona

Abstract: Older adults living with forgetfulness encounter difficulties when engaging with changing and dynamic everyday technology (ET). The capability to use ET is important for independence in later life and is affected by the contextual and individual characteristics of older adults. Using the capability approach as a theoretical lens, this phenomenological study aims to explore the experiences of older adults living with forgetfulness, in order to identify contextual and individual factors that facilitate the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Taking a qualitative approach to their work, the respective authors identified the need of social support to assist participants to learn, supporting similar findings ascertained by Marston et al (2019). Furthermore, Briones & Meijering (2021) emphasise that their research also supports intergenerational learning opportunities towards using technology, supported by previous work by Freeman et al (2020).…”
Section: Introducing the Paperssupporting
confidence: 73%
See 2 more Smart Citations
“…Taking a qualitative approach to their work, the respective authors identified the need of social support to assist participants to learn, supporting similar findings ascertained by Marston et al (2019). Furthermore, Briones & Meijering (2021) emphasise that their research also supports intergenerational learning opportunities towards using technology, supported by previous work by Freeman et al (2020).…”
Section: Introducing the Paperssupporting
confidence: 73%
“…Having individuals who support older people’s use of technology are important in technology use and uptake ( Freeman, et al, 2020 ; Marston, et al, 2019 ). In Briones & Meijering (2021 ), the presence of social support from people viewed as technology experts by older people helped the learning and use of the technology. Opportunities for intergenerational learning are important in this context, where older people may share their life experience with younger people’s technological expertise ( Briones & Meijering, 2021 ; Freeman et al, 2020 ).…”
Section: Barriers and Enablers To Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is essential to recognize that older adults also require targeted support when engaging with ICT. Studies such as those by Briones and Meijering (2021) have highlighted the critical role of social support provided by "technology experts" and the educational resources available through community centers. These supports are vital to ensuring that older individuals can successfully navigate and benefit from technology.…”
Section: Discussionmentioning
confidence: 99%
“…The new papers can still reflect the theoretical trend found in the analysis of this study. It validated that scholars still use the six groups of theories to study age-friendly community: (1) ecological theory [ 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 ], (2) the production of space [ 156 , 157 , 158 , 159 , 160 , 161 ], (3) social-related theories [ 98 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 ], (4) place-related theories [ 170 , 171 , 172 , 173 , 174 , 175 , 176 ], (5) governing-related theory [ 177 , 178 , 179 , 180 , 181 ], and (6) individual-centred theories [ 182 , 183 , 184 , 185 , 186 , 187 , 188 ]. In addition, more researchers find the importance of studying the social dynamic and individual experience in age-friendly community development.…”
Section: Discussionmentioning
confidence: 99%